1994
DOI: 10.1111/j.1440-1738.1994.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic systematics of chelonioid sea turtles

Abstract: Chelonioid sea turtles (Order Testudinata; Superfamily Chelonioidea) first appear in the early Cretaceous (Aptian-Albian). Their long fossil record is excellent compared to most marine tetrapods. Nonetheless, there has been no inclusive attempt to provide an analysis of cladistic relationships among this group. In this paper, the following chelonioid classification is proposed, based on 76 characters among 20 fossil and six living well-represented genera:(1) Family Cheloniidae (Coniacian to Recent)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(154 citation statements)
references
References 6 publications
(6 reference statements)
6
145
2
1
Order By: Relevance
“…nov. (figure 1a-g and electronic supplementary material) was added to the most comprehensive published phylogenetic data set of sea turtles (Hirayama 1998), which was revised as follows. The chimera taxon Osteopygis was separated into two taxa (the cranial Euclastes and postcranial Osteopygis; Parham 2005), and additional postcranial characters for Euclastes scored from E. (Erquelinnesia) gosseleti (Lynch & Parham 2003;Hirayama 1994). Modifications were also made to the codings and/or character state definitions of 12 characters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…nov. (figure 1a-g and electronic supplementary material) was added to the most comprehensive published phylogenetic data set of sea turtles (Hirayama 1998), which was revised as follows. The chimera taxon Osteopygis was separated into two taxa (the cranial Euclastes and postcranial Osteopygis; Parham 2005), and additional postcranial characters for Euclastes scored from E. (Erquelinnesia) gosseleti (Lynch & Parham 2003;Hirayama 1994). Modifications were also made to the codings and/or character state definitions of 12 characters.…”
Section: Methodsmentioning
confidence: 99%
“…While this phylogeny is similar to other previous studies (Hirayama 1998;Lehman & Tomlinson 2004), it is more pectinate. Toxochelys and Ctenochelys are no longer allied with derived Cheloniidae (sensu Hirayama 1994Hirayama , 1997Hirayama , 1998Joyce et al 2004;Lehman & Tomlinson 2004), but rather are reinterpreted as stem sea turtles outside crown Chelonioidea (an arrangement proposed elsewhere on braincase traits; see Gaffney and Meylan 1988;Hooks 1998). This hypothesis is further supported here by limb and girdle morphology, with Toxochelys and Ctenochelys retaining primitive postcranial features lost in crown chelonioids (figure 2): ischium with a well developed lateral process 64 , humerus with a capitellum that is upturned and shouldered 68 , first and second digits incorporated into paddle 78 , and femur with distinct trochanters 79 .…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diets of extinct Cretaceous protostegids remain speculative. Hirayama (1994) suggested that they might have been molluscivores, adapted to feeding on hard-shelled planktonic prey such as ammonites. This was based on their robust cranial morphology (e.g.…”
Section: Introductionmentioning
confidence: 99%